PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN KOMPETENSI TERHADAP KINERJA GURU SD SE-KOTA SEMARANG (Students' Journal of Economic and Management, 2014)
This study aims to analyze the influence of compensation, work motivation and competence on the performance of elementary school teachers throughout the city of Semarang. The population of this research consisted of 8109 people with a sample of 99 people. Data obtained directly from the source. The technique used for primary data collection is done by means of questionnaires to the respondents. The test results of determination (R²) indicates that teacher performance can be explained by the Compensation, Motivation and Competence by 76.7% while the rest is influenced by other variables outside of research. Compensation, labor and Competence Motivation jointly significant effect on teacher performance. The results of regression analysis show that , Compensation has positive and significant impact on teacher performance, work motivation positive and significant effect on the performance of teachers, and Competence positive and significant impact on teacher performance.Keywords: Compensation, Motivation, Competence and Performance teacher